Cobre em solos arenosos sob vinhedos e resposta bioquímica-fisiológica de videiras em produção - Miotto, Alcione (2012)
The use of Cu-based fungicides in the cultivation of grapevines for controlling fungal diseases results in excessive accumulation of Cu in soils, which may cause nutritional problems to plants. The present work aimed to investigate the accumulation and forms of Cu in acid sandy soils cultivated with vineyards in the Campanha Gaúcha region and the biochemical and physiological responses of grapevines in productive season. The study was conducted from 2009 to 2011 in the vineyards of the cultivar Cabernet Sauvignon, grown in the Campanha Gaúcha region, municipality of Sant Ana do Livramento, RS. First, the total (CuT) and available (CuEDTA) concentration of Cu were assessed in 19 vineyards at different ages and historic of applications of Cu-based fungicides. In addition, assessments were carried out for the vertical distribution of CuT and CuEDTA, the amount of accumulated CuT per hectare and the forms of Cu in the soil (chemical fractionation) in three vineyards aged 5, 11 and 31 years of cultivation. A soil collected from an area under natural field, near the vineyards, was used for comparison purposes. In the second part of the study, concentration and accumulation of Cu in the organs of the grapevines and the concentrations of macronutrients and biochemical parameters in leaf blades were investigated in vineyards grown in soils with increasing Cu concentrations. Tissue samples were collected from vines in the 2009/2010 and 2010/2011 vegetative cycles, at various phenological stages, before and after the application of Cu-based fungicides. The results reveal that the vineyards aged over 25 years of cultivation presented average concentrations of 90 mg kg-1 of CuT in the surface layer of the soil. Approximately 77% of the total Cu accumulated in the soil is CuEDTA, and thus potentially available to plants. The main form of accumulation of Cu in the soils of the vineyards was related to the mineral fraction (bound to iron and manganese oxides), which represented 75% of CuT, followed by the organic matter that complexes only 20% of the total. No significant changes were observed in the residual fraction of Cu, with higher bond strength, which indicates the prevalence of potentially available forms. In the grapevines, increased Cu concentrations were observed in leaves, as well as evidence of oxidative stress, which were correlated with increased concentrations of Cu in soil. However, the increased availability of Cu in soils slightly affects the concentrations and content of Cu in grapevines in productive season and does not change their nutritional status. The use of Cu-based fungicides is the main determinant of increased concentration of Cu in annual organs of grapevines, especially leaves and rachis, but the residue of Cu in the berries is not related to the amount applied to the element.